Inducible nitric oxide synthase expression is upregulated in oral submucous fibrosis - Rajendran R; Varkey Shirley (Wolters Kluwer Medknow Publications, 2007)
Objective: We tested the hypothesis that inducible nitric oxide synthase (iNOS) modulates angiogenesis in human models and this information could be extrapolated in elucidating the pathophysiology of oral submucous fibrosis (OSF). A hypothesis which looks inadequate, but is deep rooted in literature is the epithelial alteration ("atrophy") seen in OSF and the events that lead to its causation. This aspect was tried to be addressed and an alternative pathogenetic pathway for the disease is proposed. Materials and Methods: This immunohistochemical study sought to investigate the expression of iNOS in OSF samples (n= 30) a using monospecific antibody (SC- 2050, Santa Cruz Biotechnology, Inc) to the protein and also to correlate it with different grades of epithelial dysplasia associated with the disease. Twenty (20) healthy adults acted as controls. Results: iNOS staining was not demonstrated in normal oral epithelium. In oral epithelial dysplasia, staining was seen in all cases (100%) in the basal layers of the epithelium and in 30% of cases it extended into the parabasal compartments as well. iNOS staining was uniformly positive in moderate dysplasia with an increase in intensity and distribution noted as the severity of dysplasia progressed. There were highly significant differences in overall positivity for iNOS in epithelium between cases and controls (Mann-Whitney U = 11.000, Wilcoxon W = 221.00, P = 0.000). Significant comparisons were made of mild Vs moderate dysplasia (Mann-Whitney U = 48.000, P = 0.014) Conclusions: This study supports our earlier morphological assessment (image analysis) of the nature of vascularity in OSF mucosa. The significant vasodilation noticed in these cases argues against the concept of ischemic atrophy of the epithelium. This observation of vascularity and iNOS expression helped to explain the vasodilation noticed (sinusoids) in this disease; NO being a net vasodilator. The mechanism of activation of iNOS in dysplasia is difficult to explain. The role of contingent paracrine-activating factors on keratinocytes and macrophages is discussed.